P-78 Feasibility of an online toolkit to guide implementation of the carer support needs assessment tool. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Diffin, Janet; Ewing, Gail; Rowland, Christine; Grande, Gunn
Abstract : Background: The Carer Support Needs Assessment Tool (CSNAT) intervention identifies and addresses the support needs of family carers. This carer-centred approach involves a change in practice from a practitioner to carer-led process of assessment and support. Training is needed to help practitioners transition to this new way of working, and implementation support is required at an organisational level (Austin, Ewing & Grande, 2017; Diffin, Ewing, Harvey & Grande, 2018; Diffin, Ewing, Harvey & Grande, 2018). An online training and implementation toolkit was therefore developed to provide accessible and structured guidance on how to implement and embed the CSNAT intervention. Aim: To explore the feasibility and acceptability of delivering implementation training through an online format. Methods: The online toolkit has two learning components: (1) Individual: knowledge for practitioners to use the intervention, (2) Organisational: to assist a project team to plan, pilot and sustain implementation. Five UK palliative care services participated; 2–4 practitioners from each completed the toolkit. Online survey administered upon completion of each learning component for feedback on content, followed by telephone interview. Results: Fifteen practitioners completed 'Learning component 1' survey, 14 completed 'Learning component 2' survey, and 13 were interviewed. Feedback on content was positive. The most enjoyable aspects were the practical examples and the key steps to implementation being clearly detailed. The suitability of online learning was influenced by resource availability, the nature/size of the team, and individual learning styles. Variation in location of completion (work/home or both) was partly explained by availability of IT equipment, space, and time within the organisation. Whilst the majority of participants saw the value of online learning, some preferred face-to-face delivery, and so blended learning to include group discussions was deemed appropriate. Conclusions: Whilst online learning is welcomed by practitioners, organisations need to give it the same priority as attendance at face-to-face workshops and ensure sufficient resources are available to enable completion. Blended learning may help accommodate different learning preferences. Funder: NIHR CLARHC Greater Manchester.